FUTURE TEACHERS TRAINING IN THE ADDITIONAL EDUCATION ENVIRONMENT OF PEDAGOGICAL UNIVERSITY - Mikhail А. Chervonny; Tatyana V. Shvaleva; Anna A. Vlasova (Obrazovanie i Nauka, 2015)
Abstract. The purpose of the publication is to demonstrate the new ways and forms of additional education of schoolchildren and students in special structures of pedagogical universities.The research method involves the analysis of students' participation in organizing and conducting the competitive events for school children and teachers at the Additional Education Centre of Tomsk Pedagogical University.The research outcomes demonstrate the specific activities of the physical and mathematical profile students in preparation and fulfillment of competitive events for schoolchildren. The given form of pedagogical practice provides the future teachers with the necessary professional competences complying with the New Federal Educational Standards.Scientific novelty comprises the specificity of students' activities in collaboration with school teachers and children, facilitating the future teachers' competencies; the main phases of preparation and performance of the competitive events; and students’ competencies developed in the given process.The practical significance results from implementation of the present research findings in future studies related to developing the new forms of teaching practices.